2014
DOI: 10.1586/14787210.2014.979156
|View full text |Cite
|
Sign up to set email alerts
|

Management and prevention of pertussis infection in neonates

Abstract: Despite the fact that universal immunization against pertussis led to a dramatic decrease in the incidence and mortality in high-income countries, it has left a window of vulnerability for newborns. Although specific guidelines concerning management of neonatal whooping cough have not yet been developed, the present review summarizes the main available recommendations on diagnostic work-up and treatment of neonatal pertussis. Additionally, new prevention strategies are explored, including the use of an additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 95 publications
1
17
0
2
Order By: Relevance
“…Even though pertussis clinical presentation tends to be unspecific, there are some clinical features that seem to be more common in different age groups [ 14 , 30 ]. In our population, we observed that difficulty breathing and cyanosis were present in most of our patients between 29 days to 3 months old; however, we were surprised that paroxysmal coughing was also a common symptom in this age group.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though pertussis clinical presentation tends to be unspecific, there are some clinical features that seem to be more common in different age groups [ 14 , 30 ]. In our population, we observed that difficulty breathing and cyanosis were present in most of our patients between 29 days to 3 months old; however, we were surprised that paroxysmal coughing was also a common symptom in this age group.…”
Section: Main Textmentioning
confidence: 99%
“…Despite the pertussis vaccine success, cyclical outbreaks are observed every 2–5 years as they did in the prevaccine era [ 12 , 13 ]. Furthermore, the vaccination calendar has left a window of vulnerability for newborns and infants in which high morbidity and mortality rates are observed [ 14 – 17 ]. In addition, in infants younger than 3 months and neonates the increasing incidence of this infection and the sustained mortality rates have encouraged further investigation about the efficacy and safety of pertussis vaccination for pregnant women as an attempt to reduce the disease burden [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite pertussis vaccination, morbidity and mortality due to Bordetella pertussis remains high worldwide, particularly among newborns and infants aged less than three months [ 53 , 54 , 55 ]. More than 90% of fatalities occur in this age range.…”
Section: Efficacy and Needmentioning
confidence: 99%
“…10 In 2012, the Department of Health of United Kingdom started vaccination of all pregnant women in the third trimester, which was then followed by several other countries. 11 Recently, WHO has also supported pertussis immunization of all pregnant women, along with routine infant vaccination, in countries with high morbidity and mortality due to pertussis. 12 Amirthalingam et al reported a massive decrease in pertussis cases as well as those requiring hospitalization in infants less than 3 months following pertussis vaccination in pregnant women.…”
Section: Discussionmentioning
confidence: 99%